Management System of Sunnah Islamic Boarding School in Shaping Character of The Students - Fachruddin Azmi; Yusuf Hadijaya; Ahmad Syah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to determine the management of the Islamic boarding school sunnah system in shaping the character of students at the Al-Mukhlishin Modern Islamic Boarding School Tanjung Morawa. This research is qualitative research. The data collection technique is done by interview, observation, and documentation study. The sources of data in this study were the leaders of the Islamic boarding school, the head of the madrasa, the ustadz (teacher) in the teaching department, the ustadz in the parenting division, and the students of the Al-Mukhlishin Modern Islamic Boarding School in Tanjung Morawa. The results of the study indicate that the Modern Islamic Boarding School Al-Mukhlishin Tanjung Morawa has implemented management in Islamic boarding school activities in the character of santri, this can be seen from the management functions implemented by these functions, including planning, implementation, and evaluation.